PENINGKATAN KETERAMPILAN MENULIS PARAGRAF MELALUI METODE DEMONSTRASI DAN MEDIA MAKET DENAH SEKOLAH PADA SISWA KELAS III SDN GUNUNGSARI 3 KECAMATAN KASREMAN KABUPATEN NGAWI TAHUN PELAJARAN 2023/2024 - Ekowati, Sri Mei; Soleh, Dwi Rohman; Hadi, Panji Kuncoro (Universitas PGRI Madiun, 2024)
This study aims to describe the use of demonstration methods with school plan mockup media to improve paragraph writing skills, student learning outcomes, and the obstacles encountered for 3rd grade students at SDN Gunungsari 3. This Classroom Action Research (CAR) involved 9 students, with data collected through tests, non-tests, observation, interviews, and documentation. The results showed that the average student score increased from 59 (pre-cycle) to 70 (Cycle I) and 81 (Cycle II), with 89% of students scoring above the minimum criteria. Obstacles came from infrastructure and other factors.